Transition to e-government in Developing countries: The Case of Driver and Vehicle Licensing Authority (DVLA) e-Service Smart City Initiatives in Ghana - Joseph K. Wireko; Knud E. Skouby (International Telecommunications Society (ITS), 2016)
Beside its cost-efficient benefits, e-government plays an important role in reducing corruption. As most developing countries, especially in Africa are fighting corruption, e-government is seen as a new way of addressing it. E-government is thought to reduce corruption through increased transparency, better accountability and, the disappearance of the “middle-man” in the acquisition of public services by the citizenry. This paper tries to find out how e-government can decrease corruption by analyzing the implementation of e-government service of the Driver and Vehicle Licensing Authority (DVLA) of Ghana using the “stages of growth” mode from socio-technical perspective. The outcome of the analysis suggests that the e-government service implementation by DVLA is still at its basic and rudimentary stage (Catalogue stage) and continuous presence of the “middle-man,” high level of corruption, lack of transparency, accountability and trust in the acquisition of services provided by the Authority. The DVLA can still benefit from e-government if it commits to full implementation.
Keywords: 330; Corruption; E-government; E-service; Internet; Website